ERANAN ERGONOMI PADA TRANPORTASI PASIEN DI RUMAH SAKIT - ., Zulfiwati; Pardede, Nelson (JURNAL GAUNG INFORMATIKA, 2015)
Hospitals are currently experiencing increasingly fierce competition with the increasing number of existing hospitals, so hospitals are required to be more competentby improving existing services, such as providing the best health services to the public and oriented to individual health. Each type and place of work has a different risk ofdanger. This is influenced by location, work process, work material, and tools used in carrying out the work. One of the high-risk jobs is a hospital. In general, people andworkers in hospitals are less aware of the various potential hazards that exist.